HE 2017
DOI: 10.26762/he.2017.30000002
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and Learner Perceptions on Mobile Learning Technology: A Case of Namibian High Schools from the Hardap Region

Abstract: Although the National ICT Policy for Education in Namibia was adopted in 2005, immediately followed by the National ICT Policy Implementation Plan in 2006, no known studies have been undertaken so far to evaluate its implementation. This has made it difficult to ascertain the ICT/mobile learning readiness of teachers and learners. This study analyzed the perceptions of learners and teachers towards mobile learning in Namibian High Schools. A mixed method approach, comprising a baseline survey and interviews wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
3
1
1
Order By: Relevance
“…Research Question (RQ2): Our results showed that there was no significant difference between teachers' and learners' path coefficients. This is in contradiction to the findings of (Osakwe et al 2017) who found that learners were more positive towards m-learning than their teachers. However, our results showed that the structural model can be used to predict m-learning acceptance for both teachers and learners.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Research Question (RQ2): Our results showed that there was no significant difference between teachers' and learners' path coefficients. This is in contradiction to the findings of (Osakwe et al 2017) who found that learners were more positive towards m-learning than their teachers. However, our results showed that the structural model can be used to predict m-learning acceptance for both teachers and learners.…”
Section: Discussioncontrasting
confidence: 99%
“…Thoughts and feelings play a very important part in rejecting or accepting an IS. Several studies have found that teachers and learners have positive attitudes towards m-learning (Joo et al 2016;Osakwe, Nomusa & Jere 2017;Siyam 2019). This study aims at investigating rural-based STEM teachers' and learners' attitudes towards m-learning.…”
Section: Literature Review and Model Development Technology Acceptance Model Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…La digitalización de los centros ha de su buen uso puede ser un factor de éxito educativo como se evidencia en el caso descrito en escuelas rurales de Australia, permitiendo compartir los maestros especialistas a través de videoconferencias entre escuelas alejadas disminuyendo el aislamiento geográfico (Lombard & Ditton, 1997). Adicionalmente destaca el uso del correo electrónico para la mejora de las comunicaciones así como el aprendizaje colaborativo a través de dispositivos móviles debido a la mayor facilidad de contar con estos en algunos territorios (Demir & Akpinar, 2018;Mutambara et al, 2020) y las actitudes positivas de maestros y alumnos frente a ellos (Osakwe et al, 2017;Siyam, 2019).…”
Section: Uso Y Tipología De Los Recursos Digitales En Las Aulas Multigradounclassified
“…MacCallum and Jeffrey (2014) reported that students' use of online learning will remain informal until lecturers support its integration into a more formal way. Osakwe, Nomusa and Jere (2017) concluded that integration of online learning cannot be tapped into if lecturers' attitudes are not considered. Based on the assessments of Osakwe, Nomusa and Jere (2017) and Sánchez-Prieto et al (2019), it can be concluded that a successful implementation of online learning to support social distancing in HEIs, depends on lecturers' and students' acceptance of the technology.…”
Section: Introductionmentioning
confidence: 99%